Problema gotovnosti i organizatsii predsorevnovatel'noi podgotovki v gimnastike - Grigoriyants, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The aim of this research was to discover the essence of pedagogical tasks, means and methods of gymnasts (M&F) of high qualification precompetitional training to crucial competitions and system of their realization. The author of this paper offers the system of precompetitional training tested on gymnasts of high qualification on the basis of the carried out researches. It have received the positive response from the conducting coaches and athletes.